Penerapan Computational Thinking Melalui Media Permainan Robot Untuk Melatih Kemampuan Critical Thinking Siswa SMK Taruna Persada Dumai - Wenda Novayani; Memen Akbar; Yuli Fitrisia; Dini Nurmalasari; Yoanda Alim Syahbana (JITER-PM (Jurnal Inovasi Terapan - Pengabdian Masyarakat), 2023)
Computational thinking (CT) is the ability to think in formulating problems and solutions by thinking logically step by step to be able to determine an effective decision. CT can be embedded in all subjects, one of which is Science, Technology, Engineering, and Mathematics (STEM). Not all teachers are competent, and not all students are interested in it. This PkM applies computational thinking in STEM classes by providing realistic views of the STEM field to students through an educational robot game called Robot Edison. This workshop uses the pre-test and post-test methods to measure the increase in students' knowledge. Students do the pre-test questions, and after being given CT material and robot games, students work on the post-test questions. The number of students who took this test amounted to 16 people. Students experienced an increase in post-test scores for SMA-level questions by 66.7%. All students strongly agree (100%) that the material provided can improve their insights and abilities as vocational students. When playing with the Robot, the students looked enthusiastic and happy and were starting to think critically when making decisions on a problem effectively, and one group successfully completed the robot challenge in about 30 minutes